(untitled) (Brazilian Geographical Journal, 2019)
After K-P extinction, Patagonian crocodyliforms became less diverse, and scarcer in Tertiary layers. The specimen here described comes from "Puerta del Diablo" ranch at the Natural Protected Area of Paso Córdoba, southwestern of General Roca city (Río Negro province, Argentina) and was found in strata from the Chichinales Formation, Early Miocene (Colhuehuapian SALMA). MPCN-PV-174 is represented by an isolated fragment of the posterior region of the skull roof. This fragmentary material is assigned to an indeterminate Crocodyliformes. Previous contributions identified the most recent record of a crocodyliform from Patagonia as coming from the Early Oligocene. The specimen here described indicates that crocodyliforms were still present in the Early Miocene of Patagonia. This suggests that suitable habitats and climate for the existence of crocodilians were still available in northeastern Patagonia, at least.